Financial and economic shocks and trends in economic development: the experience of Latin American countries - Olga Fomina (Ибероамериканские тетради)
This article aims to the stages of economic development in Latin America, analyzes the experience of overcoming the crisis phenomena in the ﬁnancial and economic spheres. The author shows the strategies and models of the socio- economic development of Latin American countries from the beginning of the 20th century to the present days.